Scholarly Communication Librarians’ Relationship with Research Impact Metrics - Miles, Rachel A.; Sutton, Sarah; Konkiel, Stacy (My University, 2016)
As academia moves towards increasing concern with "real world" research impact, new measures of impact like altmetrics offer a more immediate picture of the broader impact of scholarship. Scholarly communication is also evolving rapidly thanks to technological advances, and with that change, questions arise surrounding the efficacy of using usage statistics and traditional citation-based metrics to understanding research impact. To understand the effect of these changes upon academic librarians, a nationwide survey was recently administered to over 13,000 academic librarians from Carnegie-classified R1 institutions. This presentation will examine differences in the awareness of various research impact metrics among scholarly communication librarians and their practices pertaining to using usage data and metrics for both job-related tasks and professional advancement.
Miles, Rachel, Sutton, Sarah, and Konkiel, Stacy. (2016). "Scholarly Communication Librarians’ Relationship with Research Impact Metrics," Panel Presentation: Finding Meaning in Metrics at the Association for Library Collections & Technical Services Scholarly Communications Interest Group and CRS Standards Committee Co-sponsored Session, American Library Association Annual Conference. (Orlando, FL). 25 June 2016. Presentation.
Keywords: altmetrics; bibliometrics; academic libraries; scholarly communication; research impact; research assessment